The reliance of budgets of EU member states on vat revenues. Implications in crisis and post-crisis periods - Maşca, Simona-Gabriela; Cuceu, Ionuţ-Constantin; Văidean, Viorela-Ligia (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The paper aims to provide quantitative background for policy prescriptions in the EU Member States facing a dependence on value added tax revenues. Our methods include a descriptive analysis and also an empirical study on the main determinants of value added tax revenues that resort to panel methodology. We conclude that preserving value added tax revenues as the main source for the state budget receipts is harder to achieve by tax rate reassessment, but is more easily attained by shaping the consumption path. If managing the value added tax rate is an unavoidable measure in some particular circumstances, more attention should be paid to confer that it is the right size in relation to the economic development
Argumenta Oeconomica, 2019, Nr 1 (42), s. 155-184
Keywords: state budget; VAT; final consumption of households; panel econometrics; EU-28